REKOMENDASI TERKAIT UNDERWRITING SURVEY PT.Ã¢â‚¬ÂXÃ¢â‚¬Â - Dewanto, Dedy (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
AbstractOne of the tasks of community service is to perform consultation to enterprises available in the community. This writing is based on consultation to PT.Ã¢â‚¬ÂXÃ¢â‚¬Â, which owns electricity supply business. The role of electricity as the main energy source for all human activities is vital. So important is the role of electricity as energy source, causing all important activities in life can be stopped, interrupted or delayed when power outages, resulting in lossess in various aspects of life. The loss aspect that has always been the main benchmark of staakeholders is the economic loss. Therefore ensuring the availability of electricy is very important. There are two main points of concern: availability and continuity of power supplies.In terms of availability of power supplies, Government continues to seek sufficient national electricity supply, through various power generation projects. In the contex continuity of power supplies, PT.Ã¢â‚¬ÂXÃ¢â‚¬Â has interest to perform routine maintenance at power plant, including transmission and distribution. On the other hand in the context of risk management, options available are performing physical risk control and financial risk control (risk transfer mechanism, ei move the risk to insurance company). This writing is intended to assist ensuring the settlement of Underwriting Survey Recommendations PT.Ã¢â‚¬ÂXÃ¢â‚¬Â(which survey already performed by Reinsurer HDI in relation to policy renewal), among others: to assist fact finding analysis; realization anlysis; constraints and suggestion analysis; site argumentation analysis; to assist in broad outline monitoring dan review, priority and impact as well benefit cost analysis on risk improvement recommendations on survey objects. The method of this community service using risk management, consisting of: risk identification, risk analysis and risk control. Risk control consist of physical risk control and financial risk control. This writing focus on physical risk control, especially pre loss reduction in relation to risk betterment from the point of view Reinsurer. The result are recommendations towards priority and risk impact on the object surveyed.Ã‚Â Keywords: electricity, supply, continuity, value chainÃ‚Â AbstrakSalah satu tugas pengabdian masyarakat adalah melakukan konsultansi pada perusahaan yang terdapat dalam masyarakat. Penulisan ini didasarkan pada konsultansi pada PT.Ã¢â‚¬ÂXÃ¢â‚¬Â yang memiliki bisnis di bidang penyediaan listrik. Peran listrik sebagai sumber energi utama bagi seluruh aktifitas kegiatan manusia sangatlah vital. Begitu pentingnya peranan listrik bagi sumber energi, menyebabkan semua aktifitas penting dalam kehidupan bisa terhenti, terganggu atau tertunda bila listrik padam, sehingga timbul kerugian di berbagai aspek kehidupan. Aspek kerugian yang selalu menjadi tolok ukur utama para pemangku kepentingan adalah kerugian ekonomi. Oleh karenanya memastikan ketersediaan listrik sangatlah penting. Ada dua hal pokok yang menjadi perhatian utama yaitu: ketersediaan pasokan listrik dan kontinuitas pasokan listrik. Dalam hal ketersediaan pasokan listrik, Pemerintah terus mengupayakan kecukupan pasokan listrik nasional, melalui berbagai proyek pembangkit tenaga listrik. Dari sisi kontinuitas pasokan listrik, PT.Ã¢â‚¬ÂXÃ¢â‚¬Â berkepentingan untuk melakukan routine maintenance pada pembangkit listrik, termasuk transmisi dan distribusi. Di sisi lain dalam konteks manajemen resiko, pilihannya adalah melakukan kendali resiko fisik dan kendali resiko finansial (risk transfer mechanism, yaitu memindahkan resiko ke pihak perusahaan asuransi). Penulisan konsultansi ini ditujukan untuk membantu memastikan penyelesaian Rekomendasi Underwriting Survey PT.Ã¢â‚¬ÂXÃ¢â‚¬Â (yang telah dilaksanakan oleh Surveyor Reasuransi Luar Negeri dalam perpanjangan polis), antara lain: membantu dalam analisa fact finding; analisa realisasi; analisa kendala pelaksanaan dan saran; analisa argumentasi manajemen site lokasi; membantu dalam garis besar monitoring dan review, analisis prioritas dan dampak serta benefit cost analysis atas pelaksanaan risk improvement recommendations atas obyek survey. Metode penulisan menggunakan manajemen resiko, yang terdiri dari: identifikasi resiko, analisa resiko dan kendali resiko. Kendali resiko terdiri dari kendali resiko fisik dan kendali resiko finansial. Penulisan ini fokus pada kendali resiko fisik, khususnya pre loss risk reduction, dalam rangka betterment risk terhadap Reasuradur Luar Negeri. Hasilnya berupa Rekomendasi atas prioritas dan dampak resiko atas obyek yang telah dilakukan asesmen.Ã‚Â Kata kunci: Listrik, pasokan, kontinuitas